2018
DOI: 10.1186/s13287-017-0755-3
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput immunophenotypic characterization of bone marrow- and cord blood-derived mesenchymal stromal cells reveals common and differentially expressed markers: identification of angiotensin-converting enzyme (CD143) as a marker differentially expressed between adult and perinatal tissue sources

Abstract: BackgroundMesenchymal stromal cells (MSC) are a heterogeneous population of multipotent progenitors used in the clinic because of their immunomodulatory properties and their ability to differentiate into multiple mesodermal lineages. Although bone marrow (BM) remains the most common MSC source, cord blood (CB) can be collected noninvasively and without major ethical concerns. Comparative studies comprehensively characterizing the MSC phenotype across several tissue sources are still lacking. This study provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 40 publications
1
47
0
1
Order By: Relevance
“…by mesenchymal stem cells of human cord blood and bonemarrow origin, suggesting that the CD147 protein is expressed by tissue-specific stem cells [30]. Thus, besides the loss of airway epithelial cells by viral infection and replication, a second component responsible for missing cellular regeneration is proposed, since stem and regenerating cells can be directly infected and lost.…”
Section: Azithromycin Induces Anti-viral Responses In Epithelial Cellmentioning
confidence: 99%
“…by mesenchymal stem cells of human cord blood and bonemarrow origin, suggesting that the CD147 protein is expressed by tissue-specific stem cells [30]. Thus, besides the loss of airway epithelial cells by viral infection and replication, a second component responsible for missing cellular regeneration is proposed, since stem and regenerating cells can be directly infected and lost.…”
Section: Azithromycin Induces Anti-viral Responses In Epithelial Cellmentioning
confidence: 99%
“…This CD147 has been also identified as a red blood cell receptor for parasite Plasmodium Falciparum [10] and a vascular receptor for Neisseria meningitidis [11]. CD147 has been described as a marker of undifferentiated embryonic stem cells [12] and is also expressed on mesenchymal stem cells [13]. In addition, a research team from Germany revealed that the cellular serine protease TMPRSS2 for SARS-CoV-2 spike protein priming is also essential for the host cell entry and spread [14].…”
Section: Introductionmentioning
confidence: 99%
“…The angiotensin converting enzyme CD143 was found to be expressed only in adult MSCs [200]. Biran et al [185] proposed a method to detect senescent cells in tissues by combining flow cytometry and image analysis in order to simultaneously acquire information about beta-galactosidase activity and cellular identity.…”
Section: Pcr Followed By Gelmentioning
confidence: 99%